PMI Agile Certified Practitioner Excel with Ease - Chandramouli, Subramanian (Always learning., 2012)
Agile, a topic of growing importance in project management, is an iterative and incremental software developmental methodology that helps organizations to be more flexible to change and to deliver workable software in a shorter span of time. PMI-ACP is the new credential offered by the Project Management Institute, and validates a practitioner's ability to understand and apply agile principles and practices. This self-study guide is essential reading for all PMI-ACP aspirants to clear the certification exam. Following an easy and a step-by-step learning approach, this book presents not only the basic agile concepts but also the latest developments in the field, based entirely on the guidelines from the Project Management Institute.